Interval Hypoxic Training in Rehabilitation Program for Adolescents with Overweight / Obesity and Comorbid Arterial Hypertension: Open-Label Randomized Study - Alexandra V. Mashanskaya; Anna V. Pogodina; Alina V. Atalyan; Lyubov V. Rychkova; Olga V. Bugun; Anastasia V. Vlasenko; Tamara V. Mandzyak; Elena E. Khramova; Olga V. Kravtsova; Tatiana A. Astahova (Вопросы современной педиатрии)
Background. Searching for new strategies for the rehabilitation of adolescents with obesity and comorbid arterial hypertension (AHT) before significant pathological changes development in the cardiovascular system remains the urgent challenge. Objective. The aim of the study was to examine the effect of interval hypoxic training (IHT) on blood pressure (BP) levels in adolescents with overweight / obesity and comorbid AHT. Methods. Adolescents aged 14-17 years with body mass index SDS ≥ 1 and grade I AHT (mean level of systolic and/or diastolic BP ≥ 95th percentile for population of corresponding age, sex and height) have been randomized to the group «aerobic training» (treadmill walking) and “aerobic training + IHT” (usage of hypoxicator in intermittent operation cycles). All patients were on subcaloric diet (10% reduction in caloric intake for given age). Primary outcome measure was the difference between groups on systolic/diastolic BP levels according to 24-hour BP monitoring after completion of training program (10 classes each). The effects of IHT on body composition (bioelectrical impedance analysis), heart rate variability and psychoemotional state (Spielberger scale, assessment of health, activity and mood) were further estimated. Results. 43 patients were assigned to the index group, and 42 — to the control group. 67 patients have completed the research program. 5 patients (12%) from the IHT group and 13 patients (31%; p = 0.029) from the control group prematurely discontinued participation in the trial due to poor exercise tolerance. The groups were comparable in baseline systolic and diastolic BP. Decrease in BP occurred in both groups after 10 workouts. There were no differences in decrease value: mean difference for SBP was 2.4 mm Hg (95% CI -6.6 ... 1.8), for DBP — 0.2 mm Hg (-3.6 ... 4.0). However, the incidence of reaching the targeted SBP (< 95th percentile for the corresponding age and sex) after completion of the treatment was recorded in 66% patients in the experimental group and in 42% patients in the control group (p = 0,047). Positive dynamics in several indicators of heart rate variability and psychoemotional state were mentioned in the IHT group. Conclusion. The IHT implementation in the complex of rehabilitation program for adolescents with overweight / obesity and AHT has no additional positive effect on BP levels. However, the incidence of reaching the targeted SBP (< 95th percentile for the corresponding age and sex) after completion of the treatment was recorded in 66% patients in the experimental group and in 42% patients in the control group (p = 0,054).